Pier Alberto Bertazzi (1945-2021) - La Redazione (La Medicina del Lavoro, 2021)
It is with great sadness that we announce the passing away of Professor Pier Alberto Bertazzi.Prof. Bertazzi graduated in Medicine in 1971 from the University of Milan, Italy. He completed his training at the University of North Carolina School of Public Health in Chapel Hill, NC and the National Institute for Occupational Safety and Health, Cincinnati, OH. For decades, he was associate and then full professor of Occupational Medicine at the University of Milan, where he served as Director of the Clinica del Lavoro “L. Devoto”, Milan, from 2001 to 2007 and then from 2010 to 2015, when he was appointed honorary professor.Starting from a clinical experience, he soon moved to occupational epidemiology: in the early eighties, he designed and implemented the Section of Occupational Epidemiology of the Clinica del Lavoro, the first of this kind in Italy, and launched the EPOCA center, with the idea of proposing a model to unify Occupational, Environmental and Clinical Epidemiology. Prof. Bertazzi was the organizer of many international courses on Methods in Occupational Epidemiology and fostered the application of epidemiological approaches to different areas of Occupational Health.In his country, he developed friendships with many colleagues from other Italian universities based on mutual esteem and a willingness to build something together, such as the multicentric schools for a doctorate in Occupational Medicine (Bari, Milan, Parma, and Pavia) and in Prevention Science (Parma, Brescia, Milan, and Trieste) sharing the enthusiasm for research, and for scouting and mentoring new generations of researchers. He was as strong as gentle, as determined as correct, aimed at building bridges rather than barriers; he was prone to reconcile people and clever at finding a way out in difficult situations, smoothing the edges and always working towards finding solutions. His contribution to the ICOH organization was valuable and long-lasting as he was among the founders of the Scientific Committee on Epidemiology in Occupational Health (EPICOH), ICOH Board Member in 2000-2003, Scientific Chairman of ICOH 2006 Congress, and at the ICOH 2009 Congress he was nominated ICOH Honorary member for his contribution to the promotion of Occupational Health.We were informed of his death just before the opening ceremony of the 83rd Congress of the Italian Society of Occupational Medicine. After the ceremony, the audience observed a minute of silence standing up for a tribute to his memory. Several scientific contributions presented in plenary sessions of the Congress highlighted the standing of his mentorship, giving rise to new generations of eminent scientists.He was the Director of this journal and contributed to its growth in many ways. When “La Medicina del Lavoro” became the official organ of the Italian Society of Occupational Medicine, he was appointed Editor-in-Chief of the journal for a full mandate, then providing full collaboration and ensuring a smooth handover to his successor, whose visits to each other were always concluded with a pleasant lunch: even though he had to follow a strict dietary regimen, it was always an occasion to enjoy a convivial pleasure and a friendly discussion of problems at hand looking for solutions.We remember Pier with great affection and gratitude for what he has given to the discipline and this journal. Continuing his commitment is the best way to keep his memory alive.We express our sincere condolences and sympathy to his family and his community.